Jesus, CEO : using ancient wisdom for visionary leadership - Jones, Laurie Beth. (New York : Hyperion, 1995)
Jones advises listeners to follow Jesus' examples as a motivational leader. She concentrates on three "strengths" in business: "self-mastery," "action," and "relationships" and she illustrates how Jesus' "strengths" can be put to use today.
Includes bibliographical references (p. [306]-309)
Keywords: Jesus Christ -- Leadership; Management -- Religious aspects -- Christianity; Success in business; Executive ability -- Biblical teaching